The Influence of Social Exclusion Types on Individuals' Willingness to Word-of-Mouth Recommendation - Wenting, Feng; Lijia, Wang; Cuixin, Gao (Frontiers in Psychology, 2022)
As the pace of modern life accelerates, social exclusion occurs more and more frequently in interpersonal interactions. The type of social exclusion can lead to different psychological needs of individuals, and thus affect the tendency of word-of-mouth (WOM) recommendation. There are three experiments in this research. Experiment 1 explores the influence of social exclusion types on the willingness of WOM recommendation. The result shows that being rejected increases individuals’ willingness of WOM recommendation, while being ignored decreases individuals’ willingness of WOM recommendation. Experiment 2 explores the internal psychological mechanism of the influence of social exclusion types on WOM recommendation behavior and proves the mediating role of psychological needs (uniqueness/relation). In experiment 3, the moderating effect of product attributes (scarcity/popularity) on the main effect is analyzed. This research is the first to explore the influence of social exclusion types on individuals’ willingness of WOM recommendation, which enriches the research on social exclusion in the field of WOM recommendation.